Gambaran kecemasan narapidana wanita di Sumatera Barat - Tria Monja Mandira; Marjohan Marjohan; Feri Fernandes (Holistik Jurnal Kesehatan, 2019)
Anxiety levels among female inmates in west Sumatra-IndonesiaBackground: Life in prison causes inmates to experience psychological problems. Some psychological problems that are often encountered in prisoners with the highest symptoms are stress, anxiety, aggressive behavior, and psychosomatic. An anxiety problem is found to be higher than other psychological problems that occur in female prisoners.Purpose: Knowing of description of anxiety levels among female prisoners in West Sumatra-Indonesia.Methods: The research was conducted by questionnaire. The type of research in this study is descriptive. Samples of 80 people were taken by purposive sampling.Results: The results showed the characteristics of female prisoners, more than half aged 18-40 years or the early adult category, more than half had high school education levels, and more than half did not work. An overview of female prisoners' anxiety is 53.8% moderate anxiety and 46.3% mild anxiety.Conclusion: The anxiety of female prisoners in West Sumatra is the most moderate anxiety. Suggestions for Correctional Institutions are expected to increase the existing counseling services and contributions from nurses who are in prison to overcome the anxiety felt by female prisoners during their sentences.Keywords: Anxiety; Prisoners; FemaleLatar Belakang: Kehidupan di dalam penjara mengakibatkan narapidana mengalami masalah psikologis. Beberapa masalah psikologis yang sering ditemui pada narapidana dengan gejala tertinggi yaitu stres, kecemasan, perilaku agresif, dan psikosomatis. Masalah kecemasan ditemukan lebih tinggi dibandingkan masalah psikologis lainnya yang terjadi pada narapidana wanita.Tujuan: Penelitian ini bertujuan mengetahui gambaran kecemasan narapidana wanita di Sumatera Barat.Metode: Jenis penelitian dengan deskriptif. Sampel sebanyak 80 orang yang diambil dengan purposive sampling. Penelitian menggunakan kuesioner.Hasil: Hasil penelitian menunjukkan karakteristik narapidana wanita yaitu lebih dari separuh berusia 18-40 tahun atau kategori dewasa awal, lebih dari separuh memiliki tingkat pendidikan SMA, dan lebih dari separuh tidak bekerja. Gambaran kecemasan narapidana wanita yaitu 53,8% kecemasan sedang dan 46,3% kecemasan ringan.Simpulan: Kecemasan narapidana wanita di Sumatera Barat yaitu paling banyak memiliki kecemasan sedang. Saran untuk Lembaga Pemasyarakatan diharapkan adanya peningkatan layanan konseling yang ada dan kontribusi dari perawat yang bertugas di lapas untuk mengatasi kecemasan yang dirasakan oleh narapidana wanita selama menjalani masa hukuman.